The problem of Peruvian doctors doing rural service: conclusions of the Segunda Convención Nacional de Médicos Serumistas 2013 - Inga Berrospi, Fiorella (2014)
In 1981, Peru was born in Rural and Urban Service Marginal Health (SERUM), a program of community service in primary care, in which health professionals participating graduates, colleges and business for the year of the profession. Currently, the SERUM is the main instrument of the Peruvian health system in the search for an adequate supply of health professionals in vulnerable populations. Achieving, inter alia, that maternal mortality decreased significantly in some parts of Peru (1), and the coverage of health personnel in extremely poor districts increased from 52% to 89% (2).